Tourism Crisis And Disaster Management And Organizational Learning In Malaysia’s Tourism Industry - Ghaderi, Zahed (2014)
The tourism industry is one of the businesses that has shown high vulnerability to various crisis events. Since past decades, a wide range of crises and disasters have affected travel and tourism worldwide, and created detrimental impacts on tourism organizations/destinations. However, crises, in some point, can be averted or their effect can be mitigated through practicing effective crisis management and in-depth organizational learning. The present study attempts to investigate the significance of organizational learning in tourism crisis and disaster management in Malaysia, and to explore the level of preparedness among organizations involved in tourism crisis management. The study employed in-depth interviews of 33 respondents within the tourism and non-tourism organizations in Malaysia. A qualitative research methodology based on snowball sampling, and semi-structured interviews were applied. The results show that Malaysia’s tourism industry was affected by various crises and disasters, but the impacts were temporary and after a short time the businesses recovered. The study further shows that organizational learning has an absolute role in effective crisis management, and those organizations that practiced double loop organizational learning were successful in managing crises. However, double loop organizational learning was subject to negligence by the majority of tourism organizations, and they intended to apply single loop organizational learning. It was also discovered that the majority of tourism industry players were unprepared for future crises and disasters and crisis preparation was largely over-looked.